The effect of Medicaid eligibility expansions on births - Marianne Bitler; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2000)
In an effort to increase the use of prenatal care by pregnant women and the utilization of medical care by children, eligibility for Medicaid was expanded dramatically for pregnant women and children during the 1980s and early 1990s. By lowering the costs of prenatal care, delivery, and child health care for some individuals, Medicaid expansions may prompt some women to give birth who otherwise would not have children or lead some women to have more children than they otherwise would have. This study uses natality data from 1983 to 1996 to examine the relationship between a state's eligibility threshold for Medicaid and birth rates among various groups. The results suggest that expansions have significant and sizable effects on births. A 10 percentage point increase in the eligibility threshold is associated with a 1.4 percent increase in the birth rate among nonblack women and a 1.0 percent increase among black women. Between 1983 and 1996, the expansions appear to have led to an average increase in the birth rate of about 10 percent.
Keywords: 330; Demography; Welfare; Public policy; Medicaid